Hyperschematia after right brain damage: a meaningful entity? - Rode, Gilles; Ronchi, Roberta; Revol, Patrice; Rossetti, Yves; Jacquin-Courtois, Sophie; Rossi, Irene; Vallar, Giuseppe (Frontiers in Human Neuroscience, 2014)
In recent years we reported three right-brain-damaged patients, who exhibited a left-sided disprortionate expansion of drawings, both by copying and from memory, contralateral to the side of the hemispheric lesion (Neurology, 67: 1801, 2006, Neurocase 14: 369, 2008). We proposed the term “hyperschematia” for such an expansion, with reference to an interpretation in terms of a lateral leftward distortion of the representation of extra-personal space, with a leftward anisometric expansion (relaxation) of the spatial medium. The symptom-complex shown by right-brain-damaged patients with “hyperschematia” includes: 1) a disproportionate leftward expansion of drawings (with possible addition of details), by copy and from memory (also in clay modeling, in one patient); 2) an overestimation of left lateral extent, when a leftward movement is required, associated with a perceptual underestimation; 4) unawareness of the disorder; 5) no unilateral spatial neglect. In most right-brain-damaged patients, left “hyperschematia” involves extra-personal space. In one patient the deficit was confined to a body part (left half-face: personal “hyperschematia”). The neural underpinnings of the disorder include damage to the fronto-temporo-parietal cortices, and subcortical structures in the right cerebral hemisphere, in the vascular territory of the middle cerebral artery. Here, four novel additional patients are reported. Finally, “hypeschematia” is reconsidered, in its clinical components, the underlying pathological mechanisms, as well as its neural underpinnings.